Kurangnya Keterampilan Komunikasi Generasi Z Memasuki Pasar Kerja - Hapsari, Rinanti; Agustina, Syarifaniaty; Wijaya, Richy; Romadona, Mia Rahma (Jurnal Pekommas, 2024)
The COVID-19 pandemic phenomenon has had a significant impact on the Z generation's readiness to enter the workforce. This generation has minimum communication skills in the workplace, such as, became an example of a lack of soft skills in the workplace. This research aims to investigate the lack of communication and ability phenomenon in the Z generation when entering the labor market. This investigation uses a qualitative approach that involves in-depth interviews. This research has involved 18 college graduates as research subjects. The result of this study has found that the majority of alumni suffered from communication barriers, which means they felt less capable of communicating. They feel inferior and have a low self-image due to a lack of capacity and competence as well as a lack of experience, therefore, it became such a big task to prepare themselves when entering the workforce, that hesitate to start a conversation for fear of making mistake, wrongs, and being impressed with dumbness. The obstacle lies in their self-limitation to change the situations and environments from being limited to technology and remote interaction to having to start over in situations and social environments. Other aspects that determine self-confidence and self-image have a major impact on the aspect of communication skills